Putting the Dyad into the Sexual Response Discussion: A Latent Class Analysis Using Ratings of Self and Partner. Issue 2 (12th February 2022) - Busby, Dean M.; Leonhardt, Nathan D.; Hanna-Walker, Veronica; Leavitt, Chelom E.
ABSTRACT: In this study we explored the sexual response process in couple relationships. With a U.S. sample of 383 mixed-sex couples we found seven different classes of couple sexual response using Dyadic Latent Class Growth Analysis for ratings of self and partner about their most recent sexual experience. These classes ranged from synchronous High Arousal (31.6%) and Medium Arousal (27.7%) groups, to a few classes where one partner had a quick arousal process and the other partner had very low levels of arousal. Couples in these classes were differentiated on their levels of accuracy in understanding what their partner was experiencing, as one class had couples where men experienced higher arousal than women in the first part of the experience, but the male partner was aware of the discrepancy (Equifinality, 6.8%, i.e. couples start at different levels of arousal but end up at the same place), and another where men experienced higher arousal than women throughout the experience, but men inaccurately thought their partner also experienced higher arousal (Inaccurate Split, 7.3%). The seven classes had significantly different values on variables measuring the quality of the specific sexual experience. These classes also significantly differed on a variety of measures assessing the overall sexual relationship and the relationship as a whole. These findings counter the argument that the sexual response cycle is uniform for most couples.